Mecistocephalus guildingii Newport, 1843, a tropical centipede with amphi-Atlantic distribution (Chilopoda: Geophilomorpha) - Bonato, Lucio; Cupul-Magaña, Fabio G.; Minelli, Alessandro (Zootaxa, 2009)
Mecistocephalus guildingii Newport, 1843 (Chilopoda: Geophilomorpha: Mecistocephalidae) is redescribed, and its geographical distribution revised and updated, after examination of 28 specimens from different localities together with critical assessment of published accounts and records. Mecistocephalus guildingii Newport, 1843 (= Mecistocephalus punctilabratus Newport, 1845, n. syn.; = Lamnonyx leonensis Cook, 1896, n. syn.; = Mecistocephalus maxillaris guadeloupensis Demange and Pereira, 1985, n. syn.) is distinguished from other Mecistocephalus species, with which it has been often confused, mainly in head elongation and some features of the clypeus. M. guildingii has been reported hitherto from less than two dozen sites on the eastern side of tropical Americas, however it is actually established in islands and coastal sites on both sides of the tropical part of the Atlantic ocean: on the American side from Bermuda through the Antilles to southern Brazil; on the African side in the Cape Verde archipelago and from Gambia to Liberia. It is also established in a locality on the Pacific coast of Mexico, and has been found occasionally inland in Brazil and in European hothouses and other disturbed anthropic sites.